Plato's epistemology how hard is it to know? - Laidlaw-Johnson, Elizabeth A. ([American university studies / 05], 1996)
The Combined Doctrine resolves the paradoxes of the refutations of the Theaetetus. It turns out that the difference between true belief and knowledge for Plato amounts to difference in states of mind